2015
DOI: 10.1039/c4em00683f
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the increased frequency of extreme sea levels in the Ganges–Brahmaputra–Meghna delta due to sea level rise and other effects of climate change

Abstract: Coastal flooding due to storm surge and high tides is a serious risk for inhabitants of the Ganges-Brahmaputra-Meghna (GBM) delta, as much of the land is close to sea level. Climate change could lead to large areas of land being subject to increased flooding, salinization and ultimate abandonment in both West Bengal, India, and Bangladesh. IPCC 5 th assessment modelling of sea level rise and estimates of subsidence rates from the EU IMPACT2C project suggest that sea level in the GBM delta region may rise by 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 44 publications
1
43
0
Order By: Relevance
“…The GDTR is also assumed uniform and constant for the entire study area and simulated period. While the projections of Kay et al (2015) support the assumption of relative small changes in GTDR over time, the observed amplification along the tributaries is not captured by SLAMM simulations. Any effect of changing coastline on the tidal range is also neglected.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The GDTR is also assumed uniform and constant for the entire study area and simulated period. While the projections of Kay et al (2015) support the assumption of relative small changes in GTDR over time, the observed amplification along the tributaries is not captured by SLAMM simulations. Any effect of changing coastline on the tidal range is also neglected.…”
Section: Discussionmentioning
confidence: 77%
“…Observations of the spring tides on the Indian side of the Sundarbans Estuarine System, by Chatterjee et al (2013), suggest that the degree and rate of amplification are not uniform and follow a complex pattern along the different distributaries, such that the observed spring tidal range for all coastal stations is always larger than 4.5 m and can be as large as 6.7 m. Results from Kay et al (2015), using a regional ocean model, suggest that the tidal range has little variation along the Sundarbans coastline and over three different epochs in the future up to 2100. SLAMM was developed primarily for the micro-tidal ranges and predominantly diurnal tides in the US and implicitly assumes that mangroves persist from Mean Lower Low Water (mean of the lower low water height each day, hereinafter referred to as MLLW) as the lower elevation boundary for this category up to an elevation equivalent to the Mean High Higher Water (mean of the higher high water height each day, hereinafter referred to as MHHW).…”
Section: Sundarbans Great Diurnal Tidal Range and Mangrove Elevation mentioning
confidence: 99%
“…Time series of discharge is specified as the upstream boundary condition, with a time series of water level for the downstream boundary condition. Discharge boundaries are generated from the output of a hydrological (INCA) model [11] and for downstream water level boundaries, tides are generated by using GCOMS [12].…”
Section: Model Descriptionmentioning
confidence: 99%
“…For RCP8.5, global mean SLR was estimated to be 0.3m and 0.63m for the time horizons 2040s and 2090s respectively (Elshemy and Khadr, 2015). Recent projections from the IPCC AR5 suggest that sea level in the northern Bay of Bengal (close to the study area) may rise between 0.1 and 0.3m by 2050 and 0.3 and 0.6m by 2100 without including local effects, such as land subsidence (Kay et al, 2015). The annual land subsidence rate of the study area is likely to be around 2.5mm (Kay et al, 2015, Dasgupta et al, 2014.…”
Section: Future Scenario Developmentmentioning
confidence: 99%
“…Recent projections from the IPCC AR5 suggest that sea level in the northern Bay of Bengal (close to the study area) may rise between 0.1 and 0.3m by 2050 and 0.3 and 0.6m by 2100 without including local effects, such as land subsidence (Kay et al, 2015). The annual land subsidence rate of the study area is likely to be around 2.5mm (Kay et al, 2015, Dasgupta et al, 2014. In this study, based on the above data and including annual land subsidence of 2.5mm, the relative mean SLR of 0.26m and 0.42m (for RCP4.5); and 0.44m and 0.76m (for RCP8.5) were used for the 2040s and 2090s, respectively.…”
Section: Future Scenario Developmentmentioning
confidence: 99%